v.7 - Sinha, R. K. (ed.) (New Delhi, 1989)
This Volume Seven studies agricultural and rural development in India's planned economic development. Agriculture and the rural sector have an overwhelming weight in the Indian economy. The essays included in the volume tell the story of Indian agriculture from stagnation to growth, analyse the factors where we have been successful, where we have failed and what should be done.
Keywords: Balance economic-India